THE PROCESS OF GAINING FAITH IN THE MOVIE ENTITLED THE INVENTION OF LYING - FIRDENTY N.I., SITI F. (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords:  Existence, Human, Theistic, God, ProcessIn balance, harmony and conformity among living things in this world that can occur through by the prevailing values. These values work as a constituent  of goodness where the goodness itself has relation to God as the regulator ofeverything. In the movie entitled The Invention of Lying tells about a man whoundergo a process of finding his true identity as a human being and understanding of the existence of God and also the values who created by God for human life.  In connection with the divine principle, Existentialism is a theory that examines the existence of God which is divided into two parts: theistic andatheistic. In theistic view, God is exist and involved in every things happens in humans life, God has a big role in it. But in the opposite, atheistics, Human do not confess any existence of God and  His in volvement. In writing this paper the author uses the theory of existentialism as the basic aproach for assessing thismovie entitled The Invention of Lying. The writer find some significant parts ofthe theistic side on the process of main character experience in understanding the existence of God and devine power in this movie.  Mark Bellison as the main character in this movie is a figure of inspiration that contributes a change of life insights to a lot of people around him. He becomes the only figure conveying concepts of God, death, afterlife, heaven andhell. He also reconstructs a concept of good human being as those who care about others. People give attention to manners and obey rules of God as the creator oflife and the universe. There are three series  in the process of understanding values of the divinity by the main character; find new faith, test of the faith and the final results. However, regardless of the final story in this film, the main character here has found the concept of devinity to prove that God is exists. In addition, people around Mark Bellison also receive Mark’s to convey the concept of God.